2017
DOI: 10.5812/mejrh.57560
|View full text |Cite
|
Sign up to set email alerts
|

Situational Anxiety among Nurses

Abstract: Background: Nurses routinely deal with anxiety. Thus, it causes several major problems for nurses and patients. This study was conducted to determine the level of situational anxiety in nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Again, more than a quarter of the current sample complied with the DASS cut off criteria for anxiety (8 and above) and among these individuals, over 10% had presented with severe anxiety. The prevalence of anxiety among nurses in our study also fell within the ranges commonly reported in the literature (ranging between 20–60%) [4,11,19,20,21,24,26,29]. Finally, levels of distress were high with over 40% of the current nursing sample complying with the DASS cut-off criteria for stress (scores of 15 and above) and once again multiple individuals presented with severe levels of distress while our prevalence rate was similar to those of other countries [32,34].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Again, more than a quarter of the current sample complied with the DASS cut off criteria for anxiety (8 and above) and among these individuals, over 10% had presented with severe anxiety. The prevalence of anxiety among nurses in our study also fell within the ranges commonly reported in the literature (ranging between 20–60%) [4,11,19,20,21,24,26,29]. Finally, levels of distress were high with over 40% of the current nursing sample complying with the DASS cut-off criteria for stress (scores of 15 and above) and once again multiple individuals presented with severe levels of distress while our prevalence rate was similar to those of other countries [32,34].…”
Section: Discussionsupporting
confidence: 86%
“…The health workforce in Australia is dominated by nurses, making them indispensable to the healthcare sector [1,2]. Nurses not only provide care and assistance to patients, but also participate in their rehabilitation, provide support to patients and their families, and advocate health education [3], playing an important role in improving and promoting health services in the community [4]. Their broad and multifaceted workload presents them with the largest amount of time spent with patients and allows them to cover all areas of the healthcare network [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, evidence has demonstrated that there are high incidence rates of anxiety (approximately 40% -46% prevalence rates) among Iranian nurses (19,20). However, a few studies have been conducted on nurses' anxiety to determine proper interventions to manage it and/or introduce the most effective intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatherapy with lavender oil extract reduces anxiety and insomnia in patients with dementia [36]. The results of other studies also showed that this plant can be used to increase the accuracy and stress relieving and analgesic effects in the treatment of healthcare staff and patients [37].…”
Section: Discussionmentioning
confidence: 98%